Implementasi Problem Based Learning untuk Meningkatkan Tanggung Jawab dan Hasil Belajar Pendidikan Pancasila - Tri Wahyuni; Fathurrohman Fathurrohman (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The study aims to improve students' attitudes of responsibility and learning outcomes of Pancasila Education of Grade VI Students of Jambe State Elementary School through the implementation of the problem based learning model. It is a Classroom Action Research carried out in two cycles, through the stages of planning, implementing actions, observation and reflection. The research location is at Jambe Wonosari Elementary School, Gunungkidul Regency, The research subjects were 16 grade VI students of the 2024/2025 academic year, The data source was obtained from the results of observations of attitudes of responsibility and student learning outcome tests in Pancasila Education Lessons. Data collection techniques and data collection instruments in the form of observation sheets and test questions, namely 20 multiple choice questions, data analysis techniques using descriptive analysis. The results of the study showed that 1) there was an increase in students' attitudes of responsibility from cycle I and cycle II which were taught using the problem based learning model, 2) there was an increase in learning outcomes of Pancasila Education of grade VI using the problem based learning model. This shows that the application of the problem based learning model is effective in improving attitudes of responsibility and learning outcomes of Pancasila Education. This study is expected to motivate educators to adopt the PBL model and is expected to provide solutions to improve learning in the classroom.